Plant-Derived Biomaterials: A Review of 3D Bioprinting and Biomedical Applications - Jovic, Thomas H.; Kungwengwe, Garikai; Mills, Adam C.; Whitaker, Iain S. (Frontiers in Mechanical Engineering, 2019)
The pursuit of appropriate, biocompatible materials is one of the primary challenges in translational bioprinting. The requirement to refine a biomaterial into a bioink places additional demands on the criteria for candidate biomaterials. The material must enable extrusion as a liquid bioink and yet be capable of maintaining its shape in the post-printing phase to yield viable tissues, organs and biological materials. Plant-derived biomaterials show great promise in harnessing both the natural strength of plant microarchitecture combined with their natural biological roles as supporters of cell growth. The aim of this review article is to outline the most widely used biomaterials derived from land plants and marine algae: nanocellulose, pectin, starch, alginate, agarose, fucoidan and carrageenan, with an in-depth focus on nanocellulose and alginate. The properties that render these materials as promising bioinks for three dimensional bioprinting is herein discussed alongside their potential in 3D bioprinting for tissue engineering, drug delivery, wound healing and implantable medical devices.